Highly Efficient Generation of Canker-Resistant Sweet Orange Enabled by an Improved CRISPR/Cas9 System - Huang, Xiaoen; Wang, Yuanchun; Wang, Nian (Frontiers in Plant Science, 2022)
Sweet orange (Citrus sinensis) is the most economically important species for the citrus industry. However, it is susceptible to many diseases including citrus bacterial canker caused by Xanthomonas citri subsp. citri (Xcc) that triggers devastating effects on citrus production. Conventional breeding has not met the challenge to improve disease resistance of sweet orange due to the long juvenility and other limitations. CRISPR-mediated genome editing has shown promising potentials for genetic improvements of plants. Generation of biallelic/homozygous mutants remains difficult for sweet orange due to low transformation rate, existence of heterozygous alleles for target genes and low biallelic editing efficacy using the CRISPR technology. Here, we report improvements in the CRISPR/Cas9 system for citrus gene editing. Based on the improvements we made previously (dicot codon optimized Cas9, tRNA for multiplexing, a modified sgRNA scaffold with high efficiency, CsU6 to drive sgRNA expression), we further improved our CRISPR/Cas9 system by choosing superior promoters (CmYLCV or CsUbi promoter) to drive Cas9 and optimizing culture temperature. This system was able to generate a biallelic mutation rate of up to 89% for Carrizo citrange and 79% for Hamlin sweet orange. Consequently, this system was used to generate canker resistant Hamlin sweet orange by mutating the effector binding element (EBE) of canker susceptibility gene CsLOB1, which is required for causing canker symptoms by Xcc. Six biallelic Hamlin sweet orange mutant lines in the EBE were generated. The biallelic mutants are resistant to Xcc. Biallelic mutation of the EBE region abolishes the induction of CsLOB1 by Xcc. This study represents a significant improvement in sweet orange gene editing efficacy and generating disease resistant varieties via CRISPR-mediated genome editing. This improvement in citrus genome editing makes genetic studies and manipulations of sweet orange more feasible.